Optimizing peak reduction carriers for OFDM based broadband systems - Ting, Sie King (Universiti Malaysia Sarawak, UNIMAS, 2008)
Many techniques have been applied for peak-to-average power ratio (PPAPR) reduction. The use of peak reduction carrier (PRC) scheme proposed by Lawrey and Kikkert (1999) for PAPR reduction is further investigated in this research work for the PRCs search complexity of the algorithm. A new mathematical formulation and the integration of suitable components for SA have been found for the optimum algorithm. As a result, a more efficient SA based algorithm was found with less processing time required for PAPR reduction.